2019
DOI: 10.1016/j.dam.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural parameters, tight bounds, and approximation for (k,r)-center

Abstract: In (k, r)-Center we are given a (possibly edge-weighted) graph and are asked to select at most k vertices (centers), so that all other vertices are at distance at most r from a center. In this paper we provide a number of tight fine-grained bounds on the complexity of this problem with respect to various standard graph parameters. Specifically:• For any r ≥ 1, we show an algorithm that solves the problem in O * ((3r + 1) cw ) time, where cw is the clique-width of the input graph, as well as a tight SETH lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…d ≥ O(log n)), even for the unweighted case and more restricted parameters. Figure 1 illustrates the relationships between considered parameters and summarizes our results.Related work: Our work can be considered as a continuation of the investigations in [21], where the (k, r)-Center problem is similarly studied with respect to several well-known structural parameters and a number of fine-grained upper/lower bounds is presented, while some of the techniques employed for our SETH lower bound are also present in [8].The SETH-based lower bound of (2 − ) tw · n O(1) on the running time of any algorithm for Independent Set parameterized by tw comes from [24]. For d-Scattered Set, Halldórsson et al [17] showed a tight inapproximability ratio of n 1− for even d and n 1/2− for odd d, while Eto et al [13] showed that on r-regular graphs the problem is APX-hard for r, d ≥ 3, while also providing polynomial-time O(r d−1 )-approximations and a polynomial-time approximation scheme (PTAS) for planar graphs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…d ≥ O(log n)), even for the unweighted case and more restricted parameters. Figure 1 illustrates the relationships between considered parameters and summarizes our results.Related work: Our work can be considered as a continuation of the investigations in [21], where the (k, r)-Center problem is similarly studied with respect to several well-known structural parameters and a number of fine-grained upper/lower bounds is presented, while some of the techniques employed for our SETH lower bound are also present in [8].The SETH-based lower bound of (2 − ) tw · n O(1) on the running time of any algorithm for Independent Set parameterized by tw comes from [24]. For d-Scattered Set, Halldórsson et al [17] showed a tight inapproximability ratio of n 1− for even d and n 1/2− for odd d, while Eto et al [13] showed that on r-regular graphs the problem is APX-hard for r, d ≥ 3, while also providing polynomial-time O(r d−1 )-approximations and a polynomial-time approximation scheme (PTAS) for planar graphs.…”
mentioning
confidence: 99%
“…Related work: Our work can be considered as a continuation of the investigations in [21], where the (k, r)-Center problem is similarly studied with respect to several well-known structural parameters and a number of fine-grained upper/lower bounds is presented, while some of the techniques employed for our SETH lower bound are also present in [8].…”
mentioning
confidence: 99%
“…They show that the problem is FPT on unweighted map graphs for the combined parameter (k, ρ). Also for the tree-depth, k-Center is FPT [21]. Another parameter related to transportation networks is the skeleton dimension, for which it was recently shown [8] that, under ETH, no 2 2 o( √ s) · n O(1) time algorithm can compute a (2 − ε)-approximation for any ε > 0, if the skeleton dimension is s. It is not known whether this parameter yields any approximation schemes when combined with for instance k, as is the case for the highway dimension.…”
Section: Related Workmentioning
confidence: 99%
“…In fact it is even W [2]-hard [15] to compute a (2 − ε)-approximation for any ε > 0, and thus parametrizing by k does not help to overcome the polynomial-time inapproximability. For structural parameters such as the vertex-cover number or the feedback-vertex-set number the problem remains W[1]-hard [21], even when combining with the parameter k. For each of the two more general structural parameters treewidth and cliquewidth, an efficient parameterized approximation scheme (EPAS) was shown to exist [21], i.e., a (1 + ε)-approximation can be computed in f (ε, w) · n O(1) time for any ε > 0, if w is either the treewidth or the cliquewidth, and n is the number of vertices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation